Adsorption of boron from landfill leachate by peat and the effect of environmental factors. Issue 1 (1st January 2005) - Sartaj, Majid; Fernandes, Leta
Abstract : The effect of different environmental factors including drying, shaking, soil-to-solution ratio, competing ions, solution composition, time, pH, and temperature on adsorption of boron from landfill leachate by peat was investigated. The statistical comparison of experimental results showed that shaking of adsorption samples, soil-to-solution ratio, long-term adsorption, and competing ions did not have any significant effect on boron adsorption. However, solution composition, drying of peat prior to adsorption tests, pH, and temperature had a significant effect on the adsorption of boron by peat. Diluting leachate samples with distilled water had a negative effect on the adsorption capacity. Drying peat significantly reduced its boron adsorption capacity. Boron adsorption reached maximum level at a pH range of 9–9.5. Temperature had a negative effect on the adsorption of boron. The results of two-level factorial design experiments showed that pH had the strongest effect on the adsorption of boron by peat. Key words : boron, peat, landfill, leachate, adsorption, pH, temperature, factorial design.